Detection of neutrinos from micro-quasars II - Mosquera, Mercedes Elisa (2012)
Considering a system composed of a compact object and a star subrounded by wind, and using models for high-energy proton emission from micro-quasars, we calculate the neutrino flux resulting from protonproton collisions, with and without including neutrino oscillations. It is found that the flux of neutrinos from a windy micro-quasar is affected by neutrino oscillations, and that it reflects upon the increase in the time of observation, by a factor of the order 23. © 2012 World Scientific Publishing Company.